Two Different Cell Populations Is an Important Clue for Diagnosis of Primary Cutaneous Adenoid Cystic Carcinoma: Immunohistochemical Study - Banu Ince Alkan; Onder Bozdogan; Müjde Karadeniz; Nazan Bozdoğan (Case Reports in Pathology)
Primary cutaneous adenoid cystic carcinoma (PCACC) is a very rare malignancy. The differential diagnosis of PCACCs in pathology practice can be difficult and a group of primary and metastatic lesions, including adenoid basal cell carcinoma of the skin, should be considered in the differential diagnosis. Besides histomorphological clues, immunohistochemistry studies are very helpful in the differential diagnosis of PCACC. We report herein a case of PCACC with extensive immunohistochemical studies and review the literature from an immunohistochemistry perspective.